The population prevalence of symptomatic radiographic foot osteoarthritis in community-dwelling older adults: cross-sectional findings from the Clinical Assessment Study of the Foot. Issue 1 (19th November 2013) - Roddy, Edward; Thomas, Martin J; Marshall, Michelle; Rathod, Trishna; Myers, Helen; Menz, Hylton B; Thomas, Elaine; Peat, George
Abstract : Objectives: To estimate the population prevalence of symptomatic radiographic osteoarthritis (OA) affecting the 1st metatarsophalangeal joint (MTPJ), 1st and 2nd cuneometatarsal joints (CMJs), navicular first cuneiform joint (NCJ) and talonavicular joint (TNJ) in community-dwelling older adults. Methods: 9334 adults aged ≥50 years registered with four general practices were mailed a health survey. Responders reporting foot pain within the last 12 months were invited to undergo weight-bearing dorso-plantar and lateral radiographs of both feet. OA at the 1st MTPJ, 1st and 2nd CMJs, NCJ and TNJ was graded using a validated atlas. Population prevalence estimates for symptomatic radiographic foot OA overall and for each joint were calculated using multiple imputation and weighted logistic regression modelling to account for missing data and non-response. Results: 5109 health surveys were received (adjusted response 56%). Radiographs were obtained on 557 participants. Overall population prevalence of symptomatic radiographic OA was 16.7% (95% CI 15.3% to 18.0%), 1st MTPJ 7.8% (6.7% to 8.9%), 1st CMJ 3.9% (2.9% to 4.9%), 2nd CMJ 6.8% (5.7% to 7.8%), NCJ 5.2% (4.0% to 6.4%) and TNJ 5.8% (4.8% to 6.9%). With the exception of the 1st CMJ, prevalence was greater in females than males, increased with age and was higher in lower socioeconomic classes. Three-quarters of those with symptomatic radiographic OA reported disabling foot symptoms. Conclusions: While cautious interpretation due to non-response is warranted, our study suggests that symptomatic radiographic foot OA affects one in six older adults and the majority report associated disability. Clinicians should consider OA as a possible cause of chronic foot pain in older people.